TINGKAT PENGETAHUAN TENTANG Diabetes mellitus DAN DETEKSI DINI DENGAN MINAT DETEKSI DINI PADA MASYARAKAT DI DESA DRONO KECAMATAN NGAWEN KABUPATEN KLATEN - Lesmana, Tedy Candra; Damayanti, Susi (STIKES Wira Husada Yogyakarta, 2017)
ABSTRACK The knowledge about Diabetes mellitus and early detection of people in Drono, Ngawen, Klaten District to early detection is low. This study was to determine the relationship between the level of knowledge about DM and early detection with interest in early detection ofpeople in Drono, Ngawen, Klaten District. This research is quantitative with cross sectional approach. Population on this study is people aged 40-59 years as many as 509 people with a sample as many as 84 people. Data were analyzed with Chi-Square. The level of knowledge about DM and early detection in a category is good as much as 78,57% and interest in early detection with a category is interest as much as 90,47%. There is a relationship between the level of knowledge about DM and early detection with interest in early detection of people in Drono, Ngawen, Klaten District Keyword: Diabetes mellitus, knowledge, interest, early detection